Imagining My Homecoming And Other Poems - Hosmillo, B. B. P. (Likhaan: The Journal of Contemporary Philippine Literature; Vol 18 No 1 (2024): LIKHAAN 18 The Journal of Contemporary Philippine Literature, 2024)
These poems are generated from a creative research on same-sex intimate partner abuse. Concepts from critical refugee and migration studies have a strong contribution in shaping the artistic procedure of this creative research. The author’s artistic procedure sets off from how migration elucidates precarity, vulnerability, and the (im)possibilities of resistance in an abusive relationship, how the production of the refugee figure shapes geographies of durable inequalities, and how migration as a social, artistic, and theoretical mo(ve)ment intercedes in the imagination of home.